The Impact of E-Commerce Live Streaming Services and Customer Engagement on Customer Loyalty at Shaqila Baby Shop - Fitriyadi, Farid; Indriastiningsih, Erna; Wahyuningsih, Dewi Hermawati (International Journal of Computer and Information System (IJCIS), 2024)
This research examines the effect of e-commerce live streaming services and customer engagement on customer loyalty at Shaqila Baby Shop, a store adapting innovative digital marketing strategies to enhance customer interactions. E-commerce live streaming services provide an interactive platform where customers engage directly with sellers, view products in real time, and receive immediate responses, fostering a personalized shopping experience. Customer engagement is another critical factor, as it involves customers' attachment to the brand through regular purchases, interactions, and feedback, all of which can increase loyalty. A quantitative approach was utilized, employing multiple linear regression analysis on data collected through structured questionnaires from a sample of 100 respondents, determined using Slovin’s formula. The validity and reliability tests confirmed the robustness of the data collection instruments. Findings reveal that e-commerce live streaming services and customer engagement each have a positive and significant impact on customer loyalty. Specifically, live streaming services enhance the overall shopping experience, while customer engagement fosters deeper connections with the brand. Furthermore, a simultaneous analysis shows that these factors collectively strengthen customer loyalty to a significant extent. This study provides valuable insights into how digital marketing innovations, such as live streaming and customer engagement efforts, can enhance customer loyalty, offering a practical model for businesses aiming to leverage e-commerce platforms effectively